Analisis Pembelajaran IPAS Materi Kondisi Perekonomian di Daerahku dengan Menggunakan Pendekatan Inkuiri - Risnawati, Retno Anjar; Indriayu, Mintasih (SAP (Susunan Artikel Pendidikan), 2024)
Many students have difficulty in understanding the science material. It happens because teachers have not used innovative learning approaches. The aims of this research are 1) to analyze the implementation of science and technology learning on economic conditions in my area using an inquiry approach, and 2) to analyze the impact of science and science learning on economic conditions in my area using an inquiry approach. This research uses a qualitative method with a descriptive approach. The results of the study show that the implementation of science and science learning on economic conditions in my area using an inquiry approach was overall carried out well according to the activity stages and syntax. The impact of learning science and science material on economic conditions in my area using an inquiry approach is that it has a large positive impact on student development, namely: students can actively participate in the learning presented, can foster students' motivation and enthusiasm for learning, can increase students' understanding, and improve student learning outcomes.